ANALISIS PERANCANGAN SISTEM INFORMASI PADA IMPORTED PETSHOP (PET STORY) - Joko Susilo (Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
Application Imported Pet Shop is developed with the language VB.NET use Visual Studio 2010. This pet shop application can be used in the computer windows basic to run this application. In this research, methods of data collection by doing observation and interviewed the owner of Imported Pet shop. Design of this system is using SDLC waterfall method, in order to the writer has a guideline to make application for the Imported Pet shop.To conclude this research, this application of Imported Pet shop can be used doing many activities in daily. Starting from customer transaction, controlling inventory stock and workers, then help to reduce error in doing work. With that result, every work in the pet shop can be done with this computer-based system.Â Keywords: application computer-based, VB-NET, Pet shop, work, technology